Where do the societal demand and the academic supply of knowledge meet? - Кангаспуро, Маркку (Мониторинг общественного мнения: экономические и социальные перемены, 2016)
Societal trust and cohesion are significant preconditions for fruitful interaction between academic research and the societal demand for knowledge produced by the academic community and experts. Societal trust is connected to the temporal dimension of community development, to the trust that decisions are based on the correct knowledge, and that the best knowledge for directing societal development is produced in the institutions established for that purpose: research and expert institutes, expert committees, universities, think tanks, etc..